Antibody Responses to SARS-COV-2 of COVID-19 Patients Based on the Disease Severity - Fenty Fenty; I Made AdiAnanda Putra (Indonesian Association of Clinical Pathologist and Medical laboratory, 2022)
Any individual infected by COVID-19 can suffer various degrees of disease such as asymptomatic symptoms, mild, moderate or severe. Response to the antibody formation in the human body can be affected by the severity of COVID-19. Many researchers have stated that patients suffering a severe COVID-19 had a more significant antibody response, proven by higher antibody titers than those suffering mild or moderate severity. This research aimed to observe the different antibody responses in COVID-19 patients based on the severity of the disease. The research was a retrospective study with a cross-sectional design. The inclusion criteria were confirmed SARS-COV-2 patients determined by RT-PCR test results with age ≥18 years old and a complete medical record taken from electronic medical records and Laboratory Information System (LIS). This study involved 100 COVID-19 patients consisting of 51% non-severe and 49% severe COVID-19. Patients in the non-severe group had a relatively lower IgM and IgG antibody response than patients in the severe group. It could be th primarily observed at the time of antibody measurement > 15 day of symptoms onset (p<0.05).